Soviet Grassroots : Citizen Participation in Local Soviet Government. - Hahn, Jeffrey W. (Princeton legacy library., 2017)
Jeffrey Hahn examines the degree to which citizens who are elected to local government in the USSR can successfully represent the interests of those who elected them. More specifically, how effectively do the mechanisms available for citizen participation in local government work in practice? What can elected deputies do to respond to the expressed needs and preferences of their constituents? Basing his conclusions on interviews with local deputies, observations of local soviets at work, and the analysis of a wide range of primary source material, the author finds that Soviet citizens do have some chances to participate meaningfully in local government and that a basis exists for the continued expansion of such participation. The elected deputy can and occasionally does play an active role as an ombudsman for those who choose to use opportunities for citizen input. Soviet Grassroots not only contributes to our empirical knowledge of political participation in the USSR but also provides a basis for speculation about the nature of political change in the Soviet system. If opportunities for effective participation in local government do exist, and they can be shown to have grown over time, then one precondition for the emergence of a "civic culture" in Soviet society already exists. Originally published in 1988. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.